Rancang Model Ontologi untuk Representasi Pengetahuan Tari Tradisional Indonesia - Pratama, Sang Putu Febri Wira (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023DO - 10.24843/JNATIA.2023.v01.i03.p01, 2023)
Indonesia is the largest archipelagic country in the world with more than 17,000 islands inhabited by approximately 255 million people, a figure that makes Indonesia the fourth most populous country in the world. This implies that there is a lot of cultural diversity in Indonesia, one of which is traditional dance. Traditional dances in various regions in Indonesia are certainly different and have their own characteristics, so they need to be well documented. The ontology knowledge base is an appropriate method used to represent information. In this project, the ontology model was built using the Protégé ontology development tool. We use the method of methontology in the development of the ontology model where this method describes each step-in detail. The ontology model built has 11 classes, 5 object properties, 8 data properties, and 72 individuals. We focus on describing the types of traditional dances from various regions in Indonesia. The testing process in the development of the ontology model by performing SPARQL queries.